If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12A + -7 = -1 Reorder the terms: -7 + 12A = -1 Solving -7 + 12A = -1 Solving for variable 'A'. Move all terms containing A to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 12A = -1 + 7 Combine like terms: -7 + 7 = 0 0 + 12A = -1 + 7 12A = -1 + 7 Combine like terms: -1 + 7 = 6 12A = 6 Divide each side by '12'. A = 0.5 Simplifying A = 0.5
| y=0.15x+0.15 | | 7-4a=2a+2-5a | | 12=6-2y | | y-1=1/5(x-3) | | solvingx^3-12x^2-6x-12=0 | | -7-x=1+x | | -(7-7a)+4a=-23+3a | | 20x^2(-3+4x)=0 | | 1/3x-5/6x=17 | | 157=11-w | | 21x+42=-3 | | 2b^2+5b-62=0 | | 4x-11=3x+3 | | 7-g=-11 | | Y=5/2-20 | | 17j-13j=16 | | 6x+8y=480 | | 2-(6x-19)=7(x-2) | | 6x=6(x+5)+6 | | 4x-8=4x+9 | | 4=-2x+36 | | 7.4x-1.1=13.7 | | 3x^2+9x-44=0 | | 4(x+6)=21 | | 8(6)+9y=36 | | 12x-4(5+3x)=20 | | c=3+2x | | 5(2c+3d)-8d= | | 2+3x=14+6x | | 2e^3x-8=32 | | 3(6z-1)-5(z+7)=8(z+1) | | -6+3y=-24 |